A chronicle of ICTs in agriculture - Engelhard, Rutger (Technical Centre for Agricultural and Rural Cooperation, 2009)
Access to ICTs gives farmers the chance to improve their incomes and increase food security. Since December 2000, ICT Update has reported on the many ways rural communities in have adopted and adapted technology to fit the environment where they live.